KRITIK TERHADAP KETIMPANGAN SOSIAL DALAM PUISI 'SAJAK SEBATANG LISONG' KARYA W. S. RENDRA: ANALISIS PERSPEKTIF SOSIALISME - Adil, Ahmad Fatwa; Hiriana, Risha; Yunus, Syarifudin (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study uses a qualitative descriptive method, which is an approach that aims to describe and analyze the social meanings contained in literary texts based on the researcher's in-depth interpretation. The poem Sajak Sebatang Lisong by W.S. Rendra is a form of sharp criticism of the social inequality that occurred during the New Order. From a socialist perspective, this poem voices the suffering of the common people, criticizes the dominance of the bourgeoisie, and highlights the inequality in access to education, employment, and national development that tends to imitate foreign systems without considering the local context. Rendra emphasizes that art and thought should side with social reality and the suffering of the people, not be separated from the lives of society. By making his poem an "emergency pamphlet," Rendra calls for resistance, class awareness, and the need for direct involvement of intellectuals and artists in the social struggle for justice and equality.